Current Strategies to Generate Human Mesenchymal Stem Cells In Vitro - Jennifer Steens; Diana Klein (Stem Cells International)
Mesenchymal stem cells (MSCs) are heterogeneous multipotent stem cells that are involved in the development of mesenchyme-derived evolving structures and organs during ontogeny. In the adult organism, reservoirs of MSCs can be found in almost all tissues where MSCs contribute to the maintenance of organ integrity. The use of these different MSCs for cell-based therapies has been extensively studied over the past years, which highlights the use of MSCs as a promising option for the treatment of various diseases including autoimmune and cardiovascular disorders. However, the proportion of MSCs contained in primary isolates of adult tissue biopsies is rather low and, thus, vigorous ex vivo expansion is needed especially for therapies that may require extensive and repetitive cell substitution. Therefore, more easily and accessible sources of MSCs are needed. This review summarizes the current knowledge of the different strategies to generate human MSCs in vitro as an alternative method for their applications in regenerative therapy.